2015
DOI: 10.1097/ana.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Mechanical Ventilation is Associated With Pulmonary Complications, Increased Length of Stay, and Unfavorable Discharge Destination Among Patients With Subdural Hematoma

Abstract: PMV is associated with pulmonary complications, increased LOS, and unfavorable discharge destination in patients with SDH. Alcohol abuse, admission GCS, and surgical evacuation are associated with PMV among patients with SDH. Future studies should investigate the role of early tracheostomy in high-risk patients and impact on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
15
0
6
Order By: Relevance
“…It has been reported that MV support was required in 3-6% of patients admitted to the ICU in the postoperative period, and the rate of failed weaning is reportedly 5-8% in all surgical patients (10)(11)(12). That said, it is known that ICU patients requiring prolonged MV in the postoperative period have a higher rate of failed weaning and a higher rate of morbidity and mortality (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that MV support was required in 3-6% of patients admitted to the ICU in the postoperative period, and the rate of failed weaning is reportedly 5-8% in all surgical patients (10)(11)(12). That said, it is known that ICU patients requiring prolonged MV in the postoperative period have a higher rate of failed weaning and a higher rate of morbidity and mortality (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Weaning was started a median 2 days[2][3][4] after intubation. The mean weaning time was 4[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] days. Of the patients, 21 (21.6%) experienced simple weaning, 36 (37.1%) experienced prolonged weaning and 40 (41.2%) experienced difficult weaning.…”
mentioning
confidence: 99%
“…Prolonged MV is associated with many complications [ 17 , 18 ], such as ventilator-associated pneumonia, ventilator-induced diaphragm dysfunction, increased use of medical resources, etc. [ 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Dari sebuah penelitian didapatkan lebih dari sepertiga pasien dengan SDH dengan riwayat intubasi sebelum operasi akan beresiko tinggi mengalami pemanjangan ventilasi mekanik pascaoperasi evakuasi hematom. 6 Pemanjangan ventilasi mekanik didefinisikan durasi intubasi lebih dari 4 hari, pedoman penatalaksanaan terbaru yang ada saat ini tidak menjelaskan strategi mengenai penyapihan atau ekstubasi pada pasien dengan COT. 5,6 Gambaran klinis, tingkat kesadaran dan kriteria ekstubasi yang menggambarkan angka keberhasilan ekstubasi terhadap pasien dengan COT masih diperdebatkan, terutama bagi pasien yang telah memenuhi kriteria ekstubasi namun belum mencapai level kesadaran untuk mempertahankan jalan nafas.…”
Section: Pendahuluanunclassified